Contrast‐Enhanced Sonographic Features Before and After Interventional Treatment of Ovarian Endometrial Cysts. (21st October 2015) - Shao, Xiao-Hui; Zhang, Li-Wei; Wang, Lu-Lu; Wang, Si-Ming; Dong, Xiao-Qiu
Abstract : Objectives: The purpose of this study was to assess contrast‐enhanced sonography features before and after interventional treatment of ovarian endometrial cysts. Methods: We retrospectively analyzed 53 patients with ovarian endometrial cysts who underwent contrast‐enhanced sonography before and after interventional treatment to assess the sonographic features of the cysts at these different times. The sonographic features and quantitative parameters for the cysts were compared before and after treatment. Results: The wash‐in mode showed rapid annular enhancement of the cyst wall and slow wash‐out with even and uneven enhancement types. Compared to the internal iliac artery, the enhancement intensity was weaker, and the wash‐in and wash‐out times were longer in the cyst wall; furthermore, all 5 quantitative parameters differed between the cyst wall and internal iliac artery. The wash‐in and wash‐out characteristics of the cysts before and after interventional treatment were almost identical. The enhancement was primarily even before treatment and uneven after treatment; the enhancement intensity was low in all cases. Although the wash‐in time before and after treatment did not differ, the wash‐out time for the cysts before treatment was significantly lower than that observed after treatment. Two quantitative parameters differed before and after treatment. Conclusions: The contrast‐enhanced sonographic features and quantitative parameters for the walls of ovarian endometrial cysts differed before and after ultrasound‐guided interventional treatment. These characteristics could be valuable for evaluating the efficacy of interventional treatment of ovarian endometrial cysts.